Subjective assessment of sedentary behavior between theory and practice: Pilot study using the “Sedentary meter” - Ana Cikač; Kaja Teraž; Saša Pišot (Exercise and Quality of Life)
Although sedentary behavior (SB) is still an under-researched area, some studies have shown a significant association between prolonged sitting and an increased risk of mortality, due to various causes, independent of physical activity. Despite the health risks, there are currently no specific guidelines for individuals to self-assess their SB. A pilot observational study was conducted as part of the »Knowledge for Health« event. A short online quiz “Sedentary meter” was developed, consisting of a pictorial scale to help event participants assess their daily sedentary time and to promote a better understanding of the associated health risks. The quiz questions were formulated based on the WHO definition of SB. The participants’ task was to subjectively estimate the amount of sedentary time in various types of SB on a typical day. The results obtained for SB could then be immediately compared with the figurative scale based on the WHO guidelines. The analysis confirmed SB (533.0±224.7 min/day) in all age groups, although possible differences according to the type of SB were noted. Despite statistically non-significant differences, those between age groups may indicate the extent to which SB can be individualized. The differences between age groups may indicate the importance of considering SB which can be targeted based on each age group's daily routine. The simple tool for accessing SB raised awareness of which specific type of SB accounts for the majority of participants' daily sedentary time. The self-critical acceptance of the “poor results” across all age groups shows the effectiveness of the initiative in raising awareness of SB issues.